USING DIGITAL EDUCATIONAL TECHNOLOGIES IN PEDAGOGICAL RESEARCH - Salgarayeva, Г.И; Asan, Г.Е (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article is devoted to the application of digital educational technologies in pedagogical research, in particular, the study of the possibilities of modern digital technologies, the description of the feasibility of their application and directions of development and use. The use of digital technologies in research activities is carried out through various forms of elearning. Various information technologies are used in organizing and conducting research using digital educational technologies. The intensive development of digitalization in all spheres of society will raise the organization and quality of research work in the field of pedagogy to a new level. The use of digital technologies as a means of educational activity is a research and most important task of pedagogical situations. The study of this issue is caused by the need to identify the conditions that most affect the implementation of its target areas.